Hyperimmunoglobulin E syndrome. - Petrova, E.; Semkova, K.; Miteva, L. (European Journal of Pediatric Dermatology, 2011)
Hyperimmunoglobulin E syndrome (HIES) is a rare immunodeficiency presenting with a triad of recurrent skin and pulmonary infections, elevated IgE and eczematous reaction. Two forms of HIES are currently recognized – autosomal-dominant and autosomal-recessive –. Treatment is symptomatic and the main therapeutic targets for HIES patients are prevention and management of infections. Systemic antistaphylococcal antibiotics are the mainstay of treatment. We report a case of HIES seen and followed up at our clinic and review the current literature. In our patient systemic acitretin and multiple courses of antibiotics led to a remarkable improvement and a remission period that has so far been maintained.